HUBUNGAN KEJADIAN MALARIA DENGAN PENGGUNAN KELAMBU DAN OBAT ANTI NYAMUK DI KELURAHAN SOTEK KABUPATEN PENAJAM PASER UTARA TAHUN 2015 - Ayu Yustikha Sari; Lisa Wahidatul Oktaviani; Yannie Isworo (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2016)
The number of cases of malaria in Sub Sotek higher than the number of cases in the disctrict of another , the latter case followed in the dictrict Rico, Buluminung, Sepan , and the last case of malaria in the village of Bukit Subur is malaria cases lows in the working area health centers Sotek ( PHC Sotek, 2014 ). This research aims to find out whether identificationof the corelatiaon incidence of malaria with of the use mosquito nets and insect repellentt At Sotek District Penajam Paser Utara, the correlation with the incidence of malaria bed nets, whether there is a relationship incidence of malaria by using mosquito repellent. This study is an observational study that analytic study method using case control study design . Data collection techniques using direct interviews , and questionnaires . The data analysis starts from coding data. Then data entry using the Software. There are currently no events malarian relationship with the use of nets with the coefficient of Contingenci ( p > 0.05 ; p = 0.290 ) risk value Odds Ratio ( OR ) of 2.500 . There was no relationship incidence of malaria by using mosquito repellent ( p > 0.05 ; p = 1.000 ) with the results of the risk Odds Ratio ( OR ) of 1000. There is no corelation with the incidence of malaria bed nets and anti mosquito in the district Sotek Penajam Paser Utara Year 2015. Thus, it is suggested that respondents are expected to continue to use anti- mosquito bed nets and drugs to prevent malaria , and familiarize out at night by not using clothing that covers arms and legs